ANALISIS STORE ATMOSPHERE DAN KUALITAS PELAYANAN TERHADAP KEPUTUSAN PEMBELIAN PADA TOKO KAKI EMPAT PETCARE - Agustin, Christina Omega; Samari; Sardanto, Rino (Prosiding Seminar Nasional Manajemen, Ekonomi dan Akuntansi, 2022)
This study aims to analyze whether the store atmosphere and service quality partially or simultaneously influence purchasing decisions at Kaki Empat Petcare. The selected population are consumers who have purchased products or service users at Kaki Empat Petcare. The total sample is 30 people by collecting data by using questionnaires. The method applied is quantitative causality by using accidental sampling. In this study, the results obtained indicate that the store atmosphere has a positive and significant effect on purchasing decisions of 0.004. Service quality also has a positive and significant effect on 0.006. Store atmosphere simultaneously with service quality has a significant and positive effect